Determination of individual disaster resilience levels of hospital staff: A case study of Kartal Dr. Lütfi Kirdar City Hospital - Üstünoldu, Emine (Journal of Safety Science and Resilience = An quan ke xue yu ren xing (Ying wen), 2024)
Istanbul is one of Turkey's most important financial and industrial centers, and it is located in a region with a high potential for seismicity. Due to its historical architecture and high level of urbanization, the city has a large population and is particularly vulnerable due to the building stock that will be affected by earthquakes. In the event of a possible earthquake in Istanbul, it is crucial that the hospital staff have high levels of disaster resilience/resilience. This is particularly important given the seismically isolated and earthquake-resistant structure of Istanbul Kartal Dr. Lütfi Kırdar City Hospital and its capacity to serve those injured by the earthquake. This study examines the resilience levels of hospital staff at Kartal Dr. Lütfi Kırdar City Hospital in the face of earthquake disasters and the various factors that affect these resilience levels. The data for this study were collected using a 13-question personal information form and the ‘Individual Disaster Resilience Assessment (IDRA)’ scale developed by DiTirro (2018). Descriptive statistics, Pearson Chi-square tests, Independent Samples T-tests, and One-Way ANOVA were used to analyze the data. The research found that the hospital staff's IDRA scores averaged 3.27. It was concluded that the mean resilience score of the participants was above the medium level. The research findings show that receiving disaster training or being prepared for disasters in advance significantly influences individual resistance/resilience. In this context, it is essential to determine the earthquake resistance levels of all healthcare workers in Istanbul, especially those at the city hospital where the study was conducted. Necessary training should be provided, and simulation-based disaster drills should be planned and integrated into in-service training programs. Additionally, projects should be developed to ensure that healthcare workers can reach their hospitals safely during disaster situations.